PENGARUH MODEL PICTURE AND PICTURE DALAM PENGEMBANGAN KETERAMPILAN MENULIS KARANGAN SISWA DI KELAS IV SDN TAGOG KECAMATAN CIPATAT - Maulana, M Iqbal (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This research is motivated by the low interest and poor composition writing skills of students due to the use of unengaging learning models. The purpose of this study is to improve the learning process and determine the effectiveness of the Picture and Picture model in enhancing composition writing skills of fourth-grade students at SDN 1 Tagog, Cipatat Subdistrict, West Bandung Regency. This study is a Classroom Action Research (CAR) conducted in three cycles. In the first cycle, students wrote compositions using black-and-white pictures; in the second cycle, using colored pictures; and in the third cycle, using colored pictures with added keywords. The results show a significant improvement in students’ writing skills. In the first cycle, only 4 out of 17 students (23.52%) achieved mastery with an average score of 56.47. In the second cycle, 13 students (76.47%) achieved mastery with an average score of 71.17. In the third cycle, 15 students (88.23%) achieved mastery with an average score of 81.76. In conclusion, the Picture and Picture model is effective in improving composition writing skills in Bahasa Indonesia learning in fourth grade.